Agreements Contracts in Indonesia : Application of the Consensualism - Zalshabila, Zhanya; Alam, Syamsul; Arifin, Muhammad Ya’rif (Faculty of Law, Universitas Muslim Indonesia, 2025)
This study aims to determine and analyze the form of application of the principle of consensualism in contract agreements made by the parties and to determine what are the impacts of the application of the principle of consensualism on the protection of the rights of the parties in the agreement. This study uses a normative research method. This study uses a normative legal method that focuses on the analysis of legal norms in laws and regulations, doctrines, and court decisions. The results of this study indicate that the application of the principle of consensualism is a fundamental principle in contract law which emphasizes that an agreement is considered valid and binding on the parties since the agreement is reached. The application of the principle of consensualism also has an impact on providing space for the parties to draft agreements according to their needs, but it can also pose a risk of injustice, especially for parties who have a weak bargaining position. Therefore, effective legal protection, contract supervision, and legal education for the community are important to overcome the negative impacts of the application of the principle of consensualism. The recommendation of this study is To protect the rights of the parties in the agreement, stricter supervision of contract practices is needed, especially in situations where one party has a weaker bargaining position. The government and related institutions are advised to strengthen regulations governing minimum standards for certain agreements.